Efficiency and Equilibrium with Dynamic Increasing Aggregate Returns Due to Demand Complementarities - Antonio Ciccone; Kiminori Matsuyama (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1996)
When do dynamic nonconvexities at the disaggregate level translate into dynamic nonconvexities at the aggregate level? We address this question in a framework where the production of differentiated intermediate inputs is subject to dynamic nonconvexities and show that the answer depends on the degree of Hicks-Allen complementarity (substitutability) between differentiated inputs. In our simplest model, a generalization of Judd (1985) and Grossman and Helpman (1991) among many others, there are dynamic nonconvexities at the aggregate level if and only differentiated inputs are Hicks-Allen complements. We also compare dynamic equilibrium and optimal allocations in the presence of aggregate dynamic nonconvexities due to Hicks-Allen complementarities between differentiated inputs.
Keywords: 330